Use of medicines in neonates and infants: A report of mothers’ practices - Ufuoma Shalom Ahwinahwi, Valentine Uche Odili, Magdalene Odunvbun, Anthony Ifeanyi Okeke, Uche Everister Soeze (Journal of Applied Pharmaceutical Science, 2023)
In developing countries, mothers of neonates and infants use medicines recommended by personnel other than the physician in the management of illnesses in their young. Mothers’ self-reported medicines use in neonates and infants as it relates to incidence, types of medicines used, reasons for use, and personnel recommending the medicines were evaluated. This cross-sectional study included mothers of children aged 1 year and under attending vaccination clinics across three senatorial districts in Delta State, Nigeria. Data which included socio-demographics, information on medicines used such names of medicines, reasons for use, duration of use, personnel recommending medicines, and other remedies used were taken. Data were analyzed using descriptive statistics and reported as percentages and proportions. Mothers of 782 children aged 1 year and under were included in the study. Incidence of medicines use was 91.3%. A total of 2,236 medicines were administered with 437 (19.5%), 646 (29.0%), 573 (25.6%), and 71 (3.2%) were recommended by the physician, nurse, mother of child, and pharmacist, respectively. Paracetamol was the most frequently used medicine (673, 30.1%) while fever and pain were the major reasons for medicines use. Majority of children were exposed to medicines use and infantile conditions were frequently treated without a physician’s advice.
Keywords: Neonates, infants, medicines use, pediatrics, mothers-reported